[12]aneN3-based single aliphatic chain modified cationic lipids as gene delivery vectors. Issue 5 (1st February 2019) - Gao, Yong-Guang; Liu, Fen-Li; Lu, Fu-Hua; Alam, Uzair; Tang, Quan; Huang, Jia-Wei; Lu, Zhong-Lin
Abstract: A series of aliphatic chain modified [12]aneN3 cationic lipids, 1a -1f, were synthesized and fully characterized with 1 H NMR, 13 C NMR, IR and high-resolution mass spectrometry. The liposomes formed from1a -1f and dioleoylphosphatidyl ethanolamine could effectively retard DNA migration, and condense DNA into spherical nanoparticles with an average size of 130–220 nm. Furthermore, the cytotoxicity of these liposomes assayed by MTT indicated their good biocompatibility in A549 and HepG2 cells. Results from cell transfection experiments proved that1c and1f exhibited higher transfection efficiency in A549 cells, which were higher than commercially reagent lipofectamine 2000. In order to study the interaction between1c, 1f and DNA, ionic strength effects and DNA release experiments were carried out，indicating that the DNA condensation induced by1c and1f was reversible, and electrostatic interaction played important roles. These results suggested that1c and1f have great potential to be efficient non-viral gene vectors. Graphical abstract: Highlights: A series of single aliphatic chain modified macrocyclic polyamine [12]aneN3 lipids were designed and synthesized. They showed strong DNA condensation ability, good biocompatibility in A549 and HepG2 cells. 1c and1f exhibited higher transfection efficiency than that of lipofectamine 2000. The structure-activity relationship studies provide us valuable information for developing non-virus gene vectors.